La valoración de los elementos de convicción en los delitos de evasión y su efecto jurídico en los autos de sobreseimiento dictados por la Unidad Judicial Penal con sede en el cantón Riobamba, durante el periodo de enero a septiembre del año 2014. - Gualoto Chalán, José Luis (2016)
Furthermore this research aims to investigate how physical abuse affects the constitutional and legal rights of the rulings in the Multicompetent Judicial Unit Colta Canton of Chimborazo province, it is considered physical abuse a devastating agent that destroys the core of society is the family, in our Chimborazo province is known as more of indigenous population, very predominant population exists in a patriarchal ideology with the tendency of oppression female, for this reason the majority rate of physical abuse in Colta Canton is by men against women, making women weak and defenseless genus within the family, thus creating a profound analysis that allows the performance and success of a project that consists in four chapters divided as follows: The first chapter titled Reference Framework, which is put into consideration: the problem statement, problem formulation, Objectives, Justification and Importance. The second chapter is Theoretical Framework, where the theme is explained from a theoretical point of view, the ideal model is designed to guide research theoretically, this chapter contains four units which are related to the theoretical field of research, this Content consists of the following: The first unit is about: Violence in the family, in which key concepts chords to domestic violence issues will be found; second unit refers to: Violence against women, just as we find concepts, theories and laws that allow development to be based on this research work; the third unit is about: The physical abuse. Etymology, which is the independent variable under investigation and analysis of this thesis; the fourth unit is about: Impact on constitutional and legal rights of judgments given, which is the dependent variable under investigation and analysis of this thesis and finally there is the fifth unit refers to the notional unit. In the third chapter called methodological framework, the hypothesis testing is done, through the interpretation of data obtained in the investigation. The methods used are: inductive, analytical and descriptive techniques used were interviews and survey. The fourth chapter is considered the conclusions and recommendations.